Maternal Anxiety and Attention Deficit Hyperactivity Disorder (ADHD) in Children - Roohallah Mirzaaghas; Yegane Kohani; Hasan baniasadi; Fateme Tara (Mashhad University of Medical Sciences, 2014)
Background & aim:  According to the previous studies, anxiety along with some other psychiatric disorders is common among mothers of children with attention deficit hyperactivity disorder (ADHD). Since maternal anxiety affects mother-child interactions, early treatment plays an important role in the prognosis of ADHD in children. This study aimed to determine the relationship between maternal anxiety and hyperactivity in children. Methods: This study was conducted on 112 mothers of ADHD children (aged 6-12 years), selected via convenience sampling from October to December 2012. The subjects lived in districts 2 and 6 of Tehran and were referred to consultation centers. Depression Anxiety Stress Scale 42 (DASS-42) and Swanson, Nolan and Pelham (SNAP-IV) questionnaires were completed by the subjects. Pearson's correlation coefficient was used for the analysis of the relationship between variables. Results: A positive correlation was found between maternal anxiety and children's hyperactivity (P=0.05). In fact, high levels of maternal anxiety are accounted for various child-rearing problems such as children's hyperactivity. Conclusion: High levels of maternal anxiety lead to child rearing problems, which in turn cause various disorders such as hyperactivity in children.